2016
DOI: 10.1177/0394632016673846
|View full text |Cite
|
Sign up to set email alerts
|

Some biological activities of pigments extracted from Micrococcus roseus (PTCC 1411) and Rhodotorula glutinis (PTCC 5257)

Abstract: The importance of replacing synthetic pigments with natural types is increasing day by day in the food industry due to the harmful effects of some synthetic pigments. Microorganisms are a major source of natural pigments, which nowadays have attracted the attention of researchers. In this study, carotenoid pigments were produced by Micrococcus roseus and Rhodotorula glutinis, and some of their biological properties such as antimicrobial, antioxidant, anticancer, and anti-inflammatory activities were evaluated.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 51 publications
(68 reference statements)
0
19
0
1
Order By: Relevance
“…Species of the genus Microccocus produce pigmented colonies which are sources of carotenoid pigments. Rostami et al (2016) showed that carotenoid pigments produced by Microccocus roseus proved to have some antioxidant, antitumor and potent antibacterial activities, in particular against Gram-positive bacteria. M. luteus has very few genes associated with secondary metabolism and possesses one of the smallest genomes from the phylum Actinobacteria , comprised of a single circular chromosome with 2.5 Mb in size (Young et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Species of the genus Microccocus produce pigmented colonies which are sources of carotenoid pigments. Rostami et al (2016) showed that carotenoid pigments produced by Microccocus roseus proved to have some antioxidant, antitumor and potent antibacterial activities, in particular against Gram-positive bacteria. M. luteus has very few genes associated with secondary metabolism and possesses one of the smallest genomes from the phylum Actinobacteria , comprised of a single circular chromosome with 2.5 Mb in size (Young et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The long-chain polyunsaturated fatty acids exhibited antibacterial activity against Propionibacterium acnes and S. aureus at the concentrations tested (32-1024 mg L À1 ) by Desbois & Lawlor (2013). Rostami et al (2016) reported that carotenoids extracted from Micrococcus roseus and Rhodotorula glutinis were able to inhibit S. enteritidis and E. coli.…”
Section: Antimicrobial Activitymentioning
confidence: 99%
“…The pigments displayed antimicrobial activity against MethicillinResistant Staphylococcus aureus (MRSA), Escherichia coli ATCC 25218 and Candida albicans. Another research reported that carotenoids pigment were able to inhibit Salmonella enteritidis (PTCC 1709) and E. coli (PTCC1260) (Rostami et al, 2016). In addition, crude extract of pigment from Streptomyces sp.…”
Section: Introductionmentioning
confidence: 99%